مكانة مستوى التخطيط على مستوى بعض الاندية الرياضية الجزائرية - سلطاني, جمال الدين; بن عودة, محمد (Institut d’Éducation Physique et Sportive mostaganem 2021/2022, 2021)
ان اﻻﻫﺘﻤﺎم المتزايد ﺑﺎﻟﺘﺨﻄﻴﻂ ﺟﻌﻞ ﻣﻨﻪ ﺟﺰءا ﻻ ﻳﺘﺠﺰأ ﻣﻦ اي ﻧﺸﺎط رﻳﺎﺿﻲ و ﻫﻮبمثابة المحرك اﻟﺮﺋﻴﺴﻲ و ﺷﺮﻳﺎن ﻛﻮن ﻫﺬﻩ اﻟﻌﻤﻠﻴﺔ ﻋﺒﺎرة ﻋﻦ ﺗﻄﻮر ﻣﺴﺘﻘﺒﻠﻲ لمواجهة التغيرات المستقبلية و ﻣﻦ ﻫﺬا ٬ الحياةﻟﺪى اﻻﻧﺪﻳﺔ اﻟﺮﻳﺎﺿﻴﺔ اﳌﻨﻄﻠﻖ اﺟﺮﻳﻨﺎ دراﺳﺔ ﻣﻴﺪاﻧﻴﺔ ﻟﻠﺘﻌﺮف ﻋﻠﻰ ﻣﻜﺎﻧﺔ اﻟﺘﺨﻄﻴﻂ اﻟﺮﻳﺎﺿﻲ ﻋﻠﻰ ﻣﺴﺘﻮى اﻻﻧﺪﻳﺔ اﻟﺮﻳﺎﺿﻴﺔ الجزائرية. ﺣﻴﺚ مدربين ﻋﻠﻰ ﻣﺴﺘﻮى اﻧﺪﻳﺔ وﻻﻳﱵ 10 ﻗﻤﻨﺎ ﺑﺘﺠﻤﻴﻊ اﻟﺒﻴﺎﻧﺎت الميدانية ﻋﻦ ﻃﺮﻳﻖ ﺗﻮزﻳﻊ اﺳﺘﺒﻴﺎن ﻋﻠﻰ ﻋﻴﻨﺔ ﺣﺠﻤﻬﺎ ﻏﻠﻴﺰان و ﻣﺴﺘﻐﺎﱎ . ﺗﻮﺻﻠﺖ اﻟﺪراﺳﺔ إﱃ ان اﻟﺘﺨﻄﻴﻂ اﻟﺮﻳﺎﺿﻲ يحتلﻣﻜﺎﻧﺔ ﻫﺎﻣﺔ ﻋﻠﻰ ﻣﺴﺘﻮى اﻻﻧﺪﻳﺔ اﻟﺮﻳﺎﺿﻴﺔ الجزائرية نجاح اﻟﻌﻤﻠﻴﺎت اﻟﺘﺪرﻳﺒﻴﺔ اﻻ اﻧﻪ ﻳﻌﺎﱐ ﻧﻘﺎﺋﺺ بالجملة في ﻋﻤﻠﻴﺔ ﺗﻨﻔﻴﺬﻩ. Summary The growing interest in planning has made it an integral part of any sporting activity and it is the main engine and lifeline for sports clubs, as this process is a future development to face future changes. From this point of view, we conducted a field study to identify the status of sports planning at the level of Algerian sports clubs. Where we collected field data by distributing a questionnaire to a sample of 10 trainers at the level of clubs in the states of Relizane and Mostaganem The study concluded that sports planning occupies an important place at the level of Algerian sports clubs. It is the secret of the success of training operations, but it suffers from shortcomings in the implementation process.
LES-2022-18
Keywords: sports planning - sports clubs - trainers - training processes / اﻟﻌﻤﻠﻴﺎت اﻟﺘﺪرﻳﺒﻴﺔ. - المدربين - اﻻﻧﺪﻳﺔ اﻟﺮﻳﺎﺿﻴﺔ ٬اﻟﺘﺨﻄﻴﻂ اﻟﺮﻳﺎﺿﻲ